Prime Minister Lee Hsien Loong officially opens SMU School of Law building and Kwa Geok Choo Law Library - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
Singapore Management University (SMU) today celebrated the official opening of its new School of Law building and the Kwa Geok Choo Law Library. Singapore’s Prime Minister Lee Hsien Loong was the Guest-of-Honour at the ceremony, which was attended by 800 distinguished guests, donors, faculty, students, and SMU’s partners in the legal fraternity. Completed in December 2016, the new School of Law building now stands as a distinctive landmark at the junction of Armenian Street and Stamford Road/Fort Canning Link. The 23,000-square-metre building contains modern facilities to enrich the learning and teaching experience of SMU law students and faculty. It will also enable the law school to deepen its engagement with its alumni, the community, as well as the legal fraternity. The building is designed to be contemporary in expression, while integrating with the architecture and urban fabric of the civic district. Additionally, it builds upon the porosity of SMU’s city campus and further promotes public access to Stamford Green and Fort Canning Park.